SUSTAINABLE AGILITY-DRIVEN CULTURE IN HUMAN RESOURCE MANAGEMENT: A PRIDE FRAMEWORK FOR FUTURE-READY ORGANIZATIONS - Aghnia Wulandari; Suryono Efendi; Hasanudin; Yonghwa Han (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research develops the PRIDE Framework to integrate five interdependent dimensions, People (People-Centric Excellence), Resilience, Innovation, Development, and Empowerment, into a unified model explaining how HRM practices drive both sustainability and agility. A systematic literature review guided by PRISMA principles was conducted, selecting peer-reviewed empirical and conceptual studies that examine HRM, organizational agility, and sustainability. Thematic synthesis and reflexive analysis produced a circular puzzle architecture representing these dimensions and their interconnections. Findings reveal that integrated people-centric policies, robust knowledge management, embedded innovation practices, continuous learning, and distributed decision-making create synergistic capabilities that enable rapid adaptation while maintaining long-term viability. Critical enablers include psychological safety, holistic wellness initiatives, adaptive learning programs, and outcome-based empowerment. The framework addresses gaps by showing sustainability and agility as complementary imperatives rather than competing priorities. Future research should validate the framework through multi-level and longitudinal studies, incorporate diverse language sources for broader context, and explore the impacts of AI-enabled HRM on each dimension. Limitations involve temporal and linguistic scope.